Stability and Control for Energy Production Parametric Dependence. (27th June 2010) - Carlini, Maurizio; Castellucci, Sonia; Guerrieri, Mirko; Honorati, Tommaso
Abstract : The activities of plant cultivation in Italy are provided by prefabricated structures that are designed to avoid any preliminary study of optical and thermal exchanges between the external environment and the green house. Designers mainly focused on the heating and cooling system to obtain climate beneficial effects on plant growth. This system involves rather significant operating costs which have driven the interests of designers, builders, and farmers to pursue constructive solutions such as the optimization and control of energy flows in the system. In this paper we take into account a model of greenhouse for plant cultivation to be located in Central Italy. For the optimal design of a greenhouse, simulations of heat exchange and flow of energy have been made in order to maximise the cooling system consumption of energy.